Tuber and Tuberous Root Development - Zierer, Wolfgang; Rüscher, David; Sonnewald, Uwe; Sonnewald, Sophia (Annual Review of Plant Biology, 2021)
Root and tuber crops have been an important part of human nutrition since the early days of humanity, providing us with essential carbohydrates, proteins, and vitamins. Today, they are especially important in tropical and subtropical regions of the world, where they help to feed an ever-growing population. Early induction and storage organ size are important agricultural traits, as they determine yield over time. During potato tuberization, environmental and metabolic status are sensed, ensuring proper timing of tuberization mediated by phloem-mobile signals. Coordinated cellular restructuring and expansion growth, as well as controlled storage metabolism in the tuber, are executed. This review summarizes our current understanding of potato tuber development and highlights similarities and differences to important tuberous root crop species like sweetpotato and cassava. Finally, we point out knowledge gaps that need to be filled before a complete picture of storage organ development can emerge.
CRIS-Team Scopus Importer:2021-07-02
Keywords: cassava; development; potato; storage root; sweetpotato; tuber